The changes of the most important quality parameters of szegedien triticale cultivars in long-term fertilization trials - Ács, Erika; Bóna, Lajos; Langó, Bernadett; Véha, Antal; Pepó, Péter; Petróczi, István (Acta Agraria Debreceniensis, 2016)
We were monitoring the quality changes of 2 triticale cultivars from Szeged (GK Rege and GK Szemes) in Fülöpszállás, Hungary, in a longterm fertilizer trial in 2012/2013 and 2013/2014. The following fertilizer combinations were used: untreated control, single applied N and single applied PK, 30 and 60 kg ha-1 N or PK, and N and PK together in 30:30, 60:60 ha-1 ratio. We measured the following quality parameters: kernel hardness, crude protein content and farinograph quality number for wholemeal flour.Based on the results, the N fertilization treatment was beneficial to the tested triticale culticars in terms of kernel hardness and protein content as both indicators increased. The efficiency of the treatment was proportional to the N dose rate. On the other hand, the applied PK treatment decreased the kernel hardness and crude protein values. On these two parameters, the PK free, and high N dosage treatment (N60P0K0) had the most positive effect. However, the single applied N dose had no significant effect on farinograph quality numbers of the wholemeal flours, but PK dose had significantly positive impact on the tested cultivars. The N30P30K30 treatment resulted in the highest farinograph quality number, thus the low PK and low N combination was the most efficient treatment. The correlation analysis of the tested quality parameters showed positive correlation (0.9965***) between kernel hardness values and crude protein contents. Nevertheless, we found strong negative correlation between kernel hardness values and the farinograph quality number of the wholemeal flours (-0.9720***), as well as in the case of crude protein contents and farinograph quality number of the wholemeal flours (-0.9796***).